2011
DOI: 10.1021/ef101572n
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Fine Particles during Flooding of Sandstones and Possible Relations to Enhanced Oil Recovery

Abstract: The mounting evidence that waterflooding of clay-containing sandstone reservoirs using floodwater with reduced salinity can enhance oil recovery, but with unpredictably large variation in responses, demands improved understanding of the underlying mechanisms. Mobilization of clays and other fines is one candidate mechanism. Flow experiments in Berea sandstone plugs were designed such that the change in their fines distribution from before to after the oil and water injections could be imaged in exactly the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…Similar findings related to mobilization of fine particles observed from the µ-CT and SEM images have been reported by others (Noiriel et al, 2005;Lebedeva et al, 2009;Kumar et al, 2010;Fogden et al, 2011). More M A N U S C R I P T ACCEPTED MANUSCRIPT 23 interestingly, Garing et al (2015) and Mangane et al (2013) clearly showed areas within the samples where pores were filled by solid particles after the experiments.…”
Section: Local Particle Displacement and Depositionsupporting
confidence: 88%
“…Similar findings related to mobilization of fine particles observed from the µ-CT and SEM images have been reported by others (Noiriel et al, 2005;Lebedeva et al, 2009;Kumar et al, 2010;Fogden et al, 2011). More M A N U S C R I P T ACCEPTED MANUSCRIPT 23 interestingly, Garing et al (2015) and Mangane et al (2013) clearly showed areas within the samples where pores were filled by solid particles after the experiments.…”
Section: Local Particle Displacement and Depositionsupporting
confidence: 88%
“…The ability to monitor fines migration simultaneously during a fluid flow experiment would complement the recent interesting work by Fogden et al (2011) and Kumar et al (2011) on the mobilization of fine particles during fluid flooding. They compared scanning electron microscopy (SEM) images of cut faces of core plugs before and after flooding experiments to demonstrate mobilization of fine particles within identical small areas.…”
Section: Other Potential Applications Of the Flow Cell And Magnetic Smentioning
confidence: 78%
“…probably needs further refinement in the future work (see experimental evidence from Fogden et al (2011)). With this modification, the expression of the erosion number in Eq.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
“…Injection of low salinity water into a saturated core of high salinity has been observed to give rise to significant reduction of permeability owing to the migration and the recapture of clay fines (Fauré et al, 1997;Fogden et al, 2011;Lever and Dawe, 1987;Mohan et al, 1993;Ryan and Gschwend, 1994;Sharma and Yortsos, 1987). There exists a critical salt concentration (CSC) below which the clay particles start to release.…”
Section: Accepted Manuscriptmentioning
confidence: 99%